The impact of food security concept, supply and demand management, domestic agriculture, and agricultural technology on Malaysia's food security: A Delphi expert consensus approach - Madhavedi, Sudhakar; Nagandran, Anjana; Hoo, Wong Chee; Reddy, Anugu Anil; Paraman, Pradeep (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines how food supply and demand management, domestic agriculture, agricultural technology, and conceptual understanding of food security influence Malaysia’s food security, aiming to align strategies with SDG2 (Zero Hunger) by 2030. A two-round Delphi method with 33 experts from Malaysia’s public and private sectors was used in this study. Qualitative insights and quantitative analyses (e.g., Kendall’s Coefficient) determined consensus on the relative importance of these dimensions. Experts identified robust food supply and demand management, strengthened domestic agriculture, and the adoption of advanced agricultural technologies as key drivers for improved food security. Although conceptual understanding is essential, it was ranked as the least critical factor. The study provides practical recommendations for policymakers, emphasizing targeted investments, improved logistics, and technological innovation. The findings contribute to food security research by offering a structured, expert-driven framework for addressing Malaysia’s food security challenges. This consensus-driven approach offers a unique, expert-validated model that contributes to both academic literature and practical policy formulation in the context of Malaysia’s evolving food security challenges.